2009
DOI: 10.1007/s12010-009-8525-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Performance of Lignocellulose Degradation Products on Industrial Cellulase Enzymes During Cellulose Hydrolysis

Abstract: This study examined the inhibition performance by the major lignocellulose degradation products, including organic acids, furan derivatives, lignin derivatives, and ethanol, on a broadly used commercial cellulase enzyme Spezyme CP (Genencor International, Rochester, NY, USA) to cellulose hydrolysis at both the well-mixing state (shaking flask) and the static state (test tube). The cellulase activity in the cellulase complex of Spezyme CP was assumed to be one single "cellulase", and the apparent kinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(51 citation statements)
references
References 15 publications
2
46
0
3
Order By: Relevance
“…The concentration ranges of acetic acid and levulinic acid in the experimental were 2.0-5.3 and 1.1-4.0 g/L, respectively, due to the different pretreated CS loadings. These concentration ranges were still not high enough to inhibit the saccharification of Accellerase 1000 enzyme (Chen et al, 2009;Jing et al, 2009) as well as the fermentation by S. cerevisiae DQ1. Therefore, the pretreated CS was used directly for SSF without any detoxification treatment.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…The concentration ranges of acetic acid and levulinic acid in the experimental were 2.0-5.3 and 1.1-4.0 g/L, respectively, due to the different pretreated CS loadings. These concentration ranges were still not high enough to inhibit the saccharification of Accellerase 1000 enzyme (Chen et al, 2009;Jing et al, 2009) as well as the fermentation by S. cerevisiae DQ1. Therefore, the pretreated CS was used directly for SSF without any detoxification treatment.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…This finding indicated that the promotion effect is not the sum of individual furans, but the synergism of these two furans. Kim et al [7] showed that 4 g/L furans have less inhibitory effect compared with the control, but Jing et al [11] reported opposite results. This contradicting finding could be due to the fact that cellulase from different origins exhibited varied performance.…”
Section: Furansmentioning
confidence: 99%
“…Weak acids (formic acid, acetic acid, and levulinic acid) and furans (5-hydroxymethylfurfural and furfural) are formed by hemicellulose de-acetylation and carbohydrate (cellulose and hemicellulose) degradation; moreover, various phenolic compounds are generated from lignin breakdown [10]. Although the inhibition effects of these inhibitors on ethanol fermentation have widely been investigated [8], the effects on enzymatic hydrolysis performance have been rarely studied [11,12]. Washing pretreated solids with water can improve enzymatic hydrolysis, indicating that some of the generated soluble materials (containing inhibitors) can decrease the enzymatic hydrolysis performance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Literature information is rather scant with regard to the extent of inhibition of the PL on the enzymatic hydrolysis reaction [22][23][24]. The composition and concentration of the degradation products varies with the type of feedstock, the chemistry, and the pretreatment process parameters such as temperature, time, pressure, pH, redox conditions, and presence of catalysts [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Pentoses form furfural while hexoses form hydroxymethylfurfural (HMF). Acetic acid is an initial product from the hydrolysis of hemicellulose, and lignin which are acetylated to some extent in the biomass [14,24]. Carboxylic acids are products of further degradation of furfural and HMF.…”
Section: Introductionmentioning
confidence: 99%